Prefabricated platinum nanomaterial matrix for MALDI-MS imaging of oligosaccharides and lipids in plant tissues - Shen, Yu-Lin; Zhuang, Si-Jia; Yang, Fan; Gong, Can; Xu, Xu (Frontiers in Plant Science, 2023)
Matrix-assisted laser desorption ionization mass spectrometry imaging (MALDI-MSI) can visualize the spatial distribution characteristics of molecules in tissues in situ, in which the matrix plays a key role. In this paper, we propose a platinum nanomaterial pre-coated matrix, which can be prepared in bulk by sputtering platinum nanoparticles onto slides using an ion sputterer and then used for MALDI-MS analysis by placing tissue sections on the matrix. We used this matrix for MALDI-MS imaging analysis of corn kernels and germinated wheat sections,and the results show that triacylglycerides were mainly distributed in the embryo of corn kernels and germinated wheat, and sugars were mainly distributed in the endosperm, with the highest content of disaccharides. It provides a simple and reliable experimental condition for analyzing the distribution of oligosaccharide and lipid components in plant tissues.